Analisis Potensi Unggulan Kabupaten Kepulauan Yapen dalam Menopang Pembangunan Provinsi Papua Tahun 2004-2008 - Tri Basuki, Agus (Unisia, 2012)
Regency Kepulauan Yapen is a new regency as a result of regional separation and is located in the area which is very closely to the neck of the bird head of Papua Province. An economic development strategy of a region must be able to identify all economic potencies of the region. Using analyses of MRP, Shift Share, LQ, Overlay and Klassen Typology, this research explores the economic potencies of Regency Kepulauan Yapen. This research reveals that the Regency has economic advantages in most sectors, except those of mining and manufacturing industries. The most advantageous sectors are those of services, finance, service companies, and construction. Other advantageous sectors are those supporting tourist industries, such as trade, hotel and restaurants. Keywords: economic development, economic potencies, advantages.